Attitude, knowledge and perception of the altruistic donation of blood in a city in Northeastern Mexico - Márquez Melgarejo, A.; Pérez Chávez, Fernando; Cazares Tamez, Rogelio; Díaz Olachea, Carlos Gabriel (UANL. Facultad de Medicina, 2015)
Objectives: To identify the causes due to which potential blood donors do not make voluntary donations: lack of knowledge, attitude, and the perception of blood donations as unwholesome. Materials and methods: We conducted a transversal, observational, descriptive, prospective, and a survey-based study of 435 subjects in Monterrey, Mexico in November of 2011. Results: 135 (31%) subjects were already donors, of which only 16 (3.6%) did it altruistically. Of the total amount of subjects, 161 (37%) were associated with some benefits from donating blood, 154 (35%) identified some kind of damage, the most mentioned was transmission of diseases with 77 (50%) mentions. The most common cause of refusal toward donation was ‘‘saving blood for a relative in need’’ with 137 (33%) mentions. Of the subjects surveyed, 55% (n = 240) refer having very few thoughts for donating blood voluntarily. Also, 360 (86%) subjects will donate without expecting something in return. Finally, 348 (80%) subjects do not remember seeing or hearing any kind of promotional information about altruistic blood donation. Conclusions: A great deal of people will donate blood altruistically without receiving any reward for doing so. 80% of the subjects do not remember seeing or hearing any kind of advertisement for blood donation which is proof of lack of adequate publicity. The analysis of perception of damages or benefits from blood donation will help in the development of more focused blood donation campaigns.